Hybrid Evaluation Method of Bridge Bearing Capacity - Pengzhen Lu; Said M. Easa; Ying Wu; Zhenyi Qi; Yizhou Zhuang (The Baltic Journal of Road and Bridge Engineering)
This study proposes a new method to assess the bearing capacity of similar bridges while avoiding the disadvantages of costly static loading tests. First, we present a detailed evaluation of the bearing capacity for a repaired pre-stressed concrete continuous-beam bridge following a ship collision. We have developed a finite element model, modified it, and combined with two other methods to evaluate its bearing capacity. The first method proposed is the bridge design code-based method, where the bearing capacity is assessed using specified design parameters. The second is the field test-based method, where the bearing capacity is evaluated using field tests combined with structural appearance observation. Considering the relative merits of these two methods, a new and improved method for bearing capacity evaluation is proposed and implemented by combining the design code, finite element model, and field loading tests. The innovation and contribution of this paper lie in obtaining modal parameters through a convenient dynamic load test to predict the static behaviour of the bridge structure based on the modified finite element model. Based on the dynamic test results, the static behaviour of the bridge, predicted by the modified finite element analysis, and the appearance test data of the bridge structure, the bearing capacity of the bridge structure is evaluated.